Pooling, tranching, and credit expansion - Bougheas, Spiros (Oxford University Press, 2014)
Traditionally banks have used securitization for expanding credit and thus their profitability. It has been well documented that, at least before the 2008 crisis, many banks were keeping a high proportion of the securities that they created on their own balance-sheets. Those securities retained included both the high-risk ‘equity’ tranche and the low-risk AAA-rated tranche. This paper builds a simple model of securitization that accounts for the above retention strategies. Banks in the model retained the equity tranche as skin in the game in order to mitigate moral hazard concerns while they post the low-risk tranche as collateral in order to take advantage of the yield curve. When variations in loan quality are introduced the predicted retention strategies match well those found in empirical studies.